Professores contratados por tempo determinado: sentimentos de um inquilinato docente - Cainelli, Clivia Martins de Oliveira (2016)
This work aims to identify and analyze the feelings of teachers hired for a temporary job at Technical School in São Paulo, since this condition of temporariness can assign them a character of "teaching tenancy." It was decided, therefore, to conduct a qualitative research, and the data seized resulted from semi-structured interviews with teachers who have worked temporary in the technical school searched, and from the information contained in the standards and documents of Technological Education Paula Souza Center (CEETEPS). The theoretical work was supported in BAUMAN (210; 2014); CASTEL (2008; 2013); CODO (2002); HUBERMAN (1989) and OLIVEIRA ( 2004; 2005; 2006, 2007; 2008; 2009) and the authors who study and discuss the transformations of modern society in relation to the labor market and its consequences on the Brazilian educational reforms, intensifying from the 1990s, with a direct interference in flexibility, temporariness and precariousness of the teaching profession. The results showed that feelings of happiness, well-being, inclusion, belonging and satisfaction emanate from the beginning and during teaching practice, especially in the classroom and the relationship with the coordinators, colleagues and students; however, when they witnessed the left of a colleague for rescission of contract, as well as when taking knowledge of the non-renewal of the contract itself, the feelings intensify in: exclusion, sadness, dissatisfaction, seizure interruption, loss, melancholy, mourning and misunderstanding.